Nanocomposite hydrogels based on embedded PLGA nanoparticles in gelatin. Issue 1 (February 2015) - Samba, Irmina; Hernandez, Rebeca; Rescignano, Nicoletta; Mijangos, Carmen; Kenny, Josè Maria
Abstract : Novel nanocomposites based on gelatin polymer networks containing poly(lactic-co-glycolide) (PLGA) nanoparticles (PLGA-NPs) were prepared and morphological, chemical and rheological properties were investigated. The successful incorporation of PLGA nanoparticles into the gelatin gels was confirmed by field emission scanning electron microscope (FESEM) and infrared spectroscopy (FT-IR). FESEM microscopy showed also a more homogeneous pore structure of the nanocomposite with respect to the primary gel. The introduction of PLGA nanospheres at a 1% w/v with respect to gelatin weight does not influence the elastic modulus of the pristine gelatin but an increase in the amount of PLGA spheres determine a negative effect on the elastic modulus. The prepared PLGA-NPs gelatin gels with biocompatible and biodegradable properties are very interesting from both applied and fundamental perspectives for a future application in biomedical and food fields for the control release of active molecules.